2020
DOI: 10.1371/journal.pone.0242356
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of sediment derived from erosion of partially-constructed road on aquatic organisms in a tropical river: The Río San Juan, Nicaragua and Costa Rica

Abstract: Throughout the humid tropics, increased land disturbance and concomitant road construction increases erosion and sediment delivery to rivers. Building road networks in developing countries is commonly a priority for international development funding based on anticipated socio-economic benefits. Yet the resulting erosion from roads, which recent studies have shown result in at least ten-fold increases in erosion rates, is not fully accounted for. While effects of road-derived sediment on aquatic ecosystems have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Consequently, this poses a significant threat to the habitat and aquatic life within the watershed. Although researchers have explored the impact of sediment on phytoplankton biomass and large invertebrate communities (Akbarimehr et al, 2016; Touma et al, 2020), further research in this area is warranted. The disruption of the soil‐water nutrient balance within the watershed due to road influences represents a critical concern in terms of its detrimental effects on the ecological environment.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this poses a significant threat to the habitat and aquatic life within the watershed. Although researchers have explored the impact of sediment on phytoplankton biomass and large invertebrate communities (Akbarimehr et al, 2016; Touma et al, 2020), further research in this area is warranted. The disruption of the soil‐water nutrient balance within the watershed due to road influences represents a critical concern in terms of its detrimental effects on the ecological environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the transport pathways and confluence process of the catchment, the terrain and spatial proximity characteristics of roads and streams were also significantly correlated with IC. Relevant studies have shown that TR should be an important factor affecting the transport efficiency of sediment-loaded runoff [7,61] by altering the velocity and erosion-deposition processes [41], and thus influencing the transport processes [52,59]. This is likely related to the fact that the transmission efficiency (distance) will be higher (farther) as slope and flow velocity increase, while the transmission efficiency (distance) will be lower (shorter) as relief degree and deposition rate increase [21,34,61].…”
Section: Relationship Between Sediment Connectivity and Environmental...mentioning
confidence: 99%
“…With the intensification of human activities such as forest logging, tourism development, and mineral mining, road-related soil erosion has increasingly attracted the attention of academic researchers and government management departments [3,4]. Although the area percentage of roads in a watershed is relatively low, they change the topographical and hydrological processes within watersheds by creating and exacerbating soil erosion [5] and affect the generation and transmission of runoff and sediment [6,7], thus significantly influencing the structure, process, and function of the watershed [1]. In mountainous watersheds that are sensitive to human activities and prone to erosion, the continuous expansion of roads through the restoration of old and abandoned roads for logging, the renovation of existing roads, and the construction of new planned roads [4] has led to fragmented forest landscapes in the watershed, disturbed water and sediment transport processes, and aggravated soil erosion, and thus seriously threatens the stability of the mountainous ecosystem [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to manage 109 transboundary basins and their ecosystems collectively, can result in conflicts among 110 nations (e.g. Rios-Touma et al, 2020). 111 112 Develop and harmonize transnational data collection and monitoring.…”
Section: Introduction 41mentioning
confidence: 99%